2012
DOI: 10.1088/0953-4075/45/22/225701
|View full text |Cite
|
Sign up to set email alerts
|

Line intensity and broadening in the In III spectrum

Abstract: Placement of thin indium (In) cylindrical plates at both ends of the narrow linear part of the glass discharge tube, far from the brass discharge electrodes, provides efficient erosion of the In atoms, which results in the high density of the indium vapour in argon and helium plasmas. In pulsed argon and helium discharges at 133 and 400 Pa flowing pressures, respectively, intense radiation has been observed in the doubly ionized indium (In III) spectrum ranging between 200 and 660 nm wavelengths. A notable aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…If marked as # then the given gA values are too unreliable for the transitions whose cancellation factor |CF| < 0.10 in our calculations with Cowan's code [12]. i Reference to the source: B-Bhatia et al [6]; B, TW-Wavelength from this work; K-Kaufman et al [7]; R-Ryabtsev et al [9]; S-Skočić et al [10]; TW-this work.…”
Section: Spectrum Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…If marked as # then the given gA values are too unreliable for the transitions whose cancellation factor |CF| < 0.10 in our calculations with Cowan's code [12]. i Reference to the source: B-Bhatia et al [6]; B, TW-Wavelength from this work; K-Kaufman et al [7]; R-Ryabtsev et al [9]; S-Skočić et al [10]; TW-this work.…”
Section: Spectrum Analysismentioning
confidence: 99%
“…The first work on the third spectrum of indium was done by Rao et al [1], followed by Lang [2], Douglas [3] and Nodwell [4]. Rao et al [1] identified 12 lines in the wavelength region 2983-5918 Å and established 13 levels belonging to the 4d 10 (5s, 6s, 7s, 5p, 6p, 5d, 6d, 4f, 5f and 5g) configurations. However, only six of those levels could be verified by later workers [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations